MANAJEMEN PELAYANAN DALAM MENINGKATKAN MINAT CALON JAMA’AH HAJI DAN UMROH PADA PT. TOUR AND TRAVEL AULIYA PERKASA ABADI DI PASAMAN BARAT - Anesta, Khaira Lasmi; Kenedi, Jon (Institut Agama Islam Negeri Metro, 2023)
This research evaluates the service management of PT. Auliya Tour and Travel in the implementation of Hajj and Umrah. The research method used is qualitative with data collection techniques through interviews, observations, and documentation. Primary data is obtained directly from the company's director, while secondary data comes from theories, documentation, and interviews. The research results indicate that PT. Auliya Tour and Travel implements service management by setting a target of approximately 5000 pilgrims per year. A clear organizational structure is used to direct the implementation towards achieving the goals. Training in manasik guidance and health checks such as meningitis vaccinations is conducted as preparation. In Mecca, there are studies conducted by mutawwif to enhance the pilgrims' insights. Supervision is carried out directly by the director and indirectly through WhatsApp applications, as well as performance reports submitted by department heads or divisions to the director. This management process aims to ensure the perfection and satisfaction of the implementation of Hajj and Umrah for the pilgrims.